In vivo assessment of genotoxicity in buccal cells of children undergoing tooth restoration - Gavić, Lidia; Goršeta, Kristina; Glavina, Domagoj; Željezić, Davor; Galić, Nada; Tadin, Antonija (Central European Journal of Public Health, 2019)
OBJECTIVES: Whereas dental materials came in direct or close contact with oral tissue, it is a great concern about the biocompatibility of those materials. This study was performed to evaluate possible DNA damage to buccal cells exposed to dental materials. METHODS: This prospective, longitudinal clinical study was conducted over a three months period. Class II restorations were placed in 60 young patients with no previous filling using one of three tested dental materials (two glass ionomers; Ketac Molar and Ionofil Molar and one compomer material; Twinky Star). DNA damage was analysed by micronucleus assays, in buccal exfoliated epithelial cells. RESULTS: In patients treated with Ketac Molar, a significant frequency of micronuclei (p = 0.027) and binucleated cells in samples taken 30 days following restoration (p = 0.029) was confirmed. In patients treated with Twinky Star, a statistically significant increase in the number of binucleated cells in samples taken after 7 and 30 days following restoration (p = 0.001 and p < 0.001, respectively) was observed. In all samples collected 90 days after treatment, there was no statistical difference in the number of any cell changes. CONCLUSION: In this study long-term biocompatibility of tested materials was confirmed. Glass ionomers and compomers are widely used materials in paediatric dentistry, and this study has proved their safety for usage in children.
Keywords: Composite Resins; dítě; složené pryskyřice; Mouth Mucosa; lidé; DNA Damage; ústní sliznice; Prospective Studies; Humans; Longitudinal Studies; Dental Restoration, Permanent; trvalá zubní náhrada; poškození DNA; prospektivní studie; longitudinální studie; Child